Advances in Anti-Diabetic Cognitive Dysfunction Effect of Erigeron Breviscapus (Vaniot) Hand-Mazz - Shanye Gu; Ziyi Zhou; Shijie Zhang; Yefeng Cai (MDPI AG, 2022)
Diabetic cognitive dysfunction (DCD) is the decline in memory, learning, and executive function caused by diabetes. Although its pathogenesis is unclear, molecular biologists have proposed various hypotheses, including insulin resistance, amyloid β hypothesis, tau protein hyperphosphorylation hypothesis, oxidative stress and neuroinflammation. DCD patients have no particular treatment options and current pharmacological regimens are suboptimal. In recent years, Chinese medicine research has shown that herbs with multi-component, multi-pathway and multi-target synergistic activities can prevent and treat DCD. Yunnan is home to the medicinal herb Erigeron breviscapus (Vant.) Hand-Mazz. (EBHM). Studies have shown that EBHM and its active components have a wide range of pharmacological effects and applications in cognitive disorders. EBHM's anti-DCD properties have been seldom reviewed. Through a literature study, we were able to evaluate the likely pathophysiology of DCD, prescribe anti-DCD medication and better grasp EBHM's therapeutic potential. EBHM's pharmacological mechanism and active components for DCD treatment were also summarized.